2013
DOI: 10.1007/s11033-013-2696-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression profiles of selected genes associated with the regenerative property and the receptivity to gene transfer during somatic embryogenesis in Triticum aestivum L.

Abstract: The physiological, biochemical and molecular mechanisms regulating the initiation of a regenerative pathway remain partially unknown. Efforts to identify the biological features that confer transformation ability, or the tendency of some cells to induce transgene silencing, would help to improve plant genetic engineering. The objective of our study was to monitor the evolution of plant cell competencies in relation to both in vitro tissue culture regeneration and the genetic transformation properties. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 196 publications
(255 reference statements)
0
11
0
Order By: Relevance
“…The stress-induced morphogenic response is thought to be part of a general acclimation strategy, whereby plant growth is redirected to reduce stress exposure (Potters et al 2007 ). Stress-related genome reprogramming has been experimentally observed during tissue culture response from wheat leaf base segments or ME explants, with the implication of genes in defense and anti-oxidation being observed during the expression of the developmental pathway in vitro (Delporte et al 2013 ; Singla et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stress-induced morphogenic response is thought to be part of a general acclimation strategy, whereby plant growth is redirected to reduce stress exposure (Potters et al 2007 ). Stress-related genome reprogramming has been experimentally observed during tissue culture response from wheat leaf base segments or ME explants, with the implication of genes in defense and anti-oxidation being observed during the expression of the developmental pathway in vitro (Delporte et al 2013 ; Singla et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the fundamentals and the molecular events underlying the morphogenic pathway induced in vitro, and the effect of the developmental route on competence in gene transfer and stable transformation (Delporte et al 2013 ), a more comprehensive study of the regeneration process was needed.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study on Pinus pinaster identified germin-like protein and ubiquitin-protein ligase as a probable marker for somatic embryogenesis cultured on high gellan gum concentration (Morel et al 2014). In contrast to that, another study during somatic embryogenesis in Triticum aestivum showed that although the expression of germin oxalate oxidase was maximum at the sixth day in embryogenic tissues, the difference of that gene expression between embryogenic versus nonembryogenic one was not significant (Delporte et al 2013). Changes in the GLP expression profile were involved in early cotyledon development in Arabidopsis (Chitteti and Peng 2007).…”
Section: Glp Expression At Early Developmental Stagesmentioning
confidence: 91%
“…2,4-D efficiently stimulates cell division, plant growth and in vitro-induced morphogenetic responses at low concentrations of 1-10 mg/L, while spraying the plants in the field with 2,4-D of a concentration of about one-thousand-fold higher (2 g/L, according to the weed control manuals) caused lethal symptoms that were similar to an auxin overdose [9]. Of note, in spite of the distinctly higher tolerance of the monocot vs. the dicot plants to the toxic effects of 2,4-D [10], similar concentrations of this substance are applied to induce SE in different plants, and relevantly, 1-2 mg/L of 2,4-D is recommended for SE induction in maize and wheat [11][12][13][14], while 1.1 mg/L of 2,4-D is effective for establishing an embryogenic culture in Arabidopsis [15].…”
Section: Auxin-and Stressor-like Activity Of 24-d In Se Inductionmentioning
confidence: 99%